2020
DOI: 10.3390/cells9030734
|View full text |Cite
|
Sign up to set email alerts
|

Innate Cytokine Induced Early Release of IFNγ and CC Chemokines from Hypoxic Human NK Cells Is Independent of Glucose

Abstract: Natural killer (NK) cells are among the first innate immune cells to arrive at sites of tissue inflammation and regulate the immune response to infection and tumors by the release of cytokines including interferon (IFN)γ. In vitro exposure to the innate cytokines interleukin 15 (IL-15) and IL-12/IL-18 enhances NK cell IFNγ production which, beyond 16 h of culture, was shown to depend on metabolic switching to glycolysis. NK effector responses are, however, rapid by comparison. Therefore, we sought to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
(134 reference statements)
1
5
0
Order By: Relevance
“…One We first decided to analyze the expression of nutrient transporters. Our data is in accordance with results published by others, confirming that the expression of nutrient transporters in NK cells can be upregulated in response to different stimuli 30,33,[37][38][39][40][41][42][43]46 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…One We first decided to analyze the expression of nutrient transporters. Our data is in accordance with results published by others, confirming that the expression of nutrient transporters in NK cells can be upregulated in response to different stimuli 30,33,[37][38][39][40][41][42][43]46 .…”
Section: Discussionsupporting
confidence: 93%
“…Considering that metabolism supports cellular functions, we hypothesized that CIML NK cells may also differ in their metabolic profile. Others have previously reported that NK cell stimulation induced an increase in the glycolytic activity 30,32,33,37,39,43,46,50 Our experiments were performed in a system with optimal conditions for NK cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study using murine NK cells showed that inhibition of glycolysis reduced IFN-γ production by NK cells when triggered by engagement of activating receptors while cytokine (IL-12/IL-18)-induced IFN-γ production remained unaffected by inhibition of glycolysis ( 23 ). Similar to murine NK cells, human cytokine-activated NK cells continued to produce IFN-γ when exposed to short-term glucose deprivation of 4 hours ( 35 ) or long-term low glucose levels (as low as 0.01 mM) for two days ( 36 ). However, CD56bright NK cells showed a defective IFN-γ production when the glycolysis rate was limited for a period of 18 hours ( 25 ) underlining the difference between CD56dim and CD56bright NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…54 In human NK cells, early cytokine responses can occur independent of glucose. 55 Long-term activation of NK cells upregulates both OXPHOS and glycolysis to meet the metabolic demands of effector function 56 supported by increased expression of nutrient transporters such as GLUT1, CD98 and CD71 following stimulation. 56,57 Inhibition of OXPHOS limits NK cell IFNγ production and degranulation, whereas glycolytic inhibition impairs cytotoxic functions such as target cell killing and degranulation.…”
Section: Murine Nk Cells Rely On Oxphos For Homeostatic Function Andmentioning
confidence: 99%